2010
DOI: 10.1007/s00270-010-9968-x
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Transcutaneous Oxygen Tension Measurements in Predicting Limb Salvage After Below-the-Knee Angioplasty: A Prospective Trial in Diabetic Patients With Critical Limb Ischemia

Abstract: Below-the-knee PTA as an isolated part of therapy was effective to prevent major amputation in more than a half of diabetic patients with CLI. TcPO₂ was a valid predictor for limb salvage, even when angiographic outcome criteria failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Redlich et al reported that TcPO 2 was a valid predictor for limb salvage in diabetic patients with CLI after infrapopliteal PTA, even when angiographic outcome criteria failed and that ABI measurement was of no prognostic value [33].…”
Section: Discussionmentioning
confidence: 98%
“…Redlich et al reported that TcPO 2 was a valid predictor for limb salvage in diabetic patients with CLI after infrapopliteal PTA, even when angiographic outcome criteria failed and that ABI measurement was of no prognostic value [33].…”
Section: Discussionmentioning
confidence: 98%
“…4,5 Indeed, although vessel patency alone cannot match patient-centered clinical end points 6 and any endovascular program has to be integrated into a network-based system of care involving different professionals, 7,8 an increased cutaneous oxygen pressure resulting from successful revascularization promotes infection clearance and ulcer granulation at a crucial time point. 9 The efficacy of percutaneous transluminal angioplasty (PTA) with conventional balloons, however, is limited by the high 12-month restenosis and target lesion revascularization (TLR) rates. 10 Loss of vessel patency affects the healing process, resulting in no healing, decrease-increase behavior of the ulcer, or appearance of new foot lesions.…”
Section: Clinical Perspective On P 621mentioning
confidence: 99%
“…6 In our hospital, non-invasive tests (pain in the lower limb, Doppler, ABI and TcPO 2 ) are performed by the nursing department in the Vascular Radiology Service, and our results are consistent with the progression of our professional activity. 4,7 We have observed that ABI cannot be determined in some cases (2.5%) or is unreliable when there is a calcified arterial medial layer (12.5% of cases), showing limitations in outcomes of success in PTA-treated patients (15% of total). 4,6,7 In this study, we monitored TcPO 2 while performing PTA revealing variations in each phase of the radiological procedure.…”
Section: Discussionmentioning
confidence: 95%
“…4,7 We have observed that ABI cannot be determined in some cases (2.5%) or is unreliable when there is a calcified arterial medial layer (12.5% of cases), showing limitations in outcomes of success in PTA-treated patients (15% of total). 4,6,7 In this study, we monitored TcPO 2 while performing PTA revealing variations in each phase of the radiological procedure. We have not found previous references for this observation except that by Wagner et al 6 that described similar changes in only one patient.…”
Section: Discussionmentioning
confidence: 95%